Integrated transcriptomics and metabolites at different growth stages reveals the regulation mechanism of bolting and flowering of Angelicasinensis. (29th April 2021) - Li, J.; Li, M.L.; Zhu, T.T.; Zhang, X.N.; Li, M.F.; Wei, J.H.
Abstract: The root of Angelica sinensis is one of the most widely used traditional Chinese medicines. In commercial planting, early bolting and flowering (EBF) of ca. 40% of 2‐year‐old plants reduces root yield and quality. Although changes in physiology in bolted plants have been investigated, the mechanism activating EBF has not been identified. Here, transcriptomics profiles at four different growth stages (S1 to S4) were performed, gene expression was validated by qRT‐PCR and the accumulation of endogenous hormones quantified by HPLC. A total of 60, 282 unigenes were generated, with 2, 282, 1, 359 and 2, 246 differentially expressed genes (DEGs) observed at S2 versus S1, S3 versus S2 and S4 versus S3, respectively; 558 genes that co‐exist in at least three stages from S1 to S4 were obtained. Functional annotation classified 38 DEGs linked to flowering pathways: photoperiodism, hormone signalling, carbohydrate metabolism and floral development. The levels of gene expression, hormones (GA1, GA4 and IAA) and soluble sugars were consistent with the EBF. It can be concluded that the EBF of A . sinensis is controlled by multiple genes. This integrated analysis of transcriptomics, together with targeted hormones and soluble sugars, provides new insights into the regulation of EBF of A . sinensis . Abstract : Bolting and flowering of Angelica sinensis is controlled by multiple genes related to photoperiodism, hormone signaling, carbohydrate metabolism and floral development.